2018
DOI: 10.1038/s41467-018-05949-0
|View full text |Cite
|
Sign up to set email alerts
|

Inducing drop to bubble transformation via resonance in ultrasound

Abstract: Bubble formation plays an important role in industries concerned with mineral flotation, food, cosmetics, and materials, which requires additional energy to produce the liquid–gas interfaces. A naturally observed fact is, owing to the effect of surface tension, a bubble film tends to retract to reduce its surface area. Here we show a “reverse” phenomenon whereby a drop is transformed into a bubble using acoustic levitation via acoustic resonance. Once the volume of the cavity encapsulated by the buckled film r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…The penetrability, shape adaptability, and self-healing ability of the liquid membrane can effectively maintain a smooth separation of two liquids. The liquid membrane typically shows dynamic reconfigurability 21 , stability, and elasticity 22 , which can be used for antifouling transport 23 , unusual particle separators 24 , biomedical fluid handling 25 and so on. In recent years, such membranes have been shown to have extensive applications in biochemistry and medicine 26 , environmental management, fossil fuel extraction, cosmetics and other industries.…”
Section: Introductionmentioning
confidence: 99%
“…The penetrability, shape adaptability, and self-healing ability of the liquid membrane can effectively maintain a smooth separation of two liquids. The liquid membrane typically shows dynamic reconfigurability 21 , stability, and elasticity 22 , which can be used for antifouling transport 23 , unusual particle separators 24 , biomedical fluid handling 25 and so on. In recent years, such membranes have been shown to have extensive applications in biochemistry and medicine 26 , environmental management, fossil fuel extraction, cosmetics and other industries.…”
Section: Introductionmentioning
confidence: 99%
“…14 Zang et al used ALM to generate bubbles for industries pertaining to inorganic salts, food, cosmetics, and materials. 15,16 Furthermore, these authors also developed a microreactor that coats solid potassium permanganate on the surface of levitated water droplets. 17,18 Xie et al demonstrated that small organisms such as insects and small sh can levitate in a living state.…”
Section: Introductionmentioning
confidence: 99%
“…The container-less nature of ALM makes this technique widely applicable in the fields of material processing, biology, and analytical chemistry, since such container-less processing can prevent nucleation and contamination due to contact with container walls [29]. For example, Zang et al applied ALM to the formation of bubbles for use in food, cosmetics, pharmaceuticals, ultra-light materials, and mineral flotation [10,11], additionally examining the spreading of potassium permanganate on the surface of levitated water droplets to develop a microreactor [12,13]. Xie et al demonstrated that small organisms, such as insects and small fish can be acoustically levitated as well [14].…”
Section: Introductionmentioning
confidence: 99%